The knowledge economy and taxes on the rich. Issue 5 (4th May 2022) - Hope, David; Limberg, Julian
ABSTRACT : What drives taxes on the rich? In this article, we claim that the existing empirical literature on taxing the rich suffers from two key shortcomings: 1) It pays too little attention to the major structural and technological changes that have taken place in advanced capitalist economies since the 1970s; and 2) it lacks consensus on how to measure taxes on the rich. We seek to address these shortcomings by exploring the implications of the rise of the knowledge economy for taxing the rich, as well as constructing a new, comprehensive measure of taxes on the rich. We then carry out a panel data analysis estimating the effect of the employment share in knowledge-intensive services on taxes on the rich in 13 OECD countries from 1970-2015. Our results show that the expansion of the knowledge economy is strongly and robustly associated with lower taxes on the rich.